Analisis Penggunaan Sequence Proton Density Spair Potongan Sagital Terhadap Kualitas Citra Anatomi Pada Pemeriksaan Mri Knee Joint Di Mayapada Hospital Jakarta Selatan - Chairiya, Chairiya (Jurnal Kesehatan Madani Medika, 2025)
This research seeks to analyze the quality of anatomical images and analyze the sequences used in knee joint MRI at South Jakarta Mayapada Hospital to have the benefit of adding insight and expertise about Knee Joint MRI examination with the use of Proton Density SPAIR sequences of Sagittal pieces. And it is hoped that it could be a reference for further research. The research design used is descriptive and qualitative with the method of collecting data by direct observation and primary data collection which was carried out from January to June 2022 at South Jakarta Mayapada Hospital. The research instruments used are worksheets and documentation tools. The population of this research was patients who performed a Lower Extremity MRI examination totaling 50 patients. The specimens used were 15 patients with Knee Joint MRI examination. Data processing and analysis uses data reduction, data presentation, and concluding data according to verification. The results of this research, in the use of the Proton Density SPAIR sequence, sagittal pieces produced a good and precise image of the meniscus, ligaments, and tendons. So it could be concluded that the Proton Density SPAIR sequence is suitable for showing anatomy and pathology at South Jakarta Mayapada Hospital.